The Influence of Toxic Leadership and Employee Engagement on Employee Performance at PT. Glory Offset Press - Akbarsyah, Mohammad (Lafadz Jaya Publisher, 2024)
This study employed a saturated sampling method where the entire population of 81 employees was used as the research sample. Data collection was conducted through questionnaires. The results revealed that toxic leadership had a negative and significant impact on employee performance, with a determination coefficient (R2) value of 0.052, indicating a 52% influence. The t-value was -2.078, which was greater than the t-table value of 1.66462, with a significance value of 0.041, less than 0.05. Meanwhile, employee engagement had a positive effect on employee performance, with a determination coefficient (R2) value of 0.137, representing a 13.7% influence. The t-value was 3.548, greater than the t-table value of 1.66462, and a significance value of 0.001, less than 0.05. Simultaneously, toxic leadership and employee engagement had a combined effect on employee performance, with an R2 value of 0.217, meaning a combined influence of 21.7%, with an F-value of 10.822, greater than the F-table value of 3.11.